Literature Review: The Application of the Borg & Gall Development Model in Science Learning - Sri Aprilia Nur Larasati; Johana Aulina Rahmatin; Rita Alawiyah; Satutik Rahayu (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The implementation of the Borg & Gall model in science education is highly significant in creating educational products that are adaptive, relevant, and based on real needs in the field. This research aims to analyze the results of a literature review on the application of the Borg & Gall development model in science education. This research uses the literature review method and data processing using descriptive analysis. Three journals related to the title determined by the researcher were obtained. Based on the literature review conducted on 3 journals regarding the development of teaching media using the Borg & Gall development model in Science Learning, it has a positive impact on improving student learning outcomes. The next interesting research to conduct is related to the application of the Borg & Gall model in other fields of study to develop knowledge related to the Borg & Gall development model.